A new species of Notocyrtus, a new synonym of Coilopus, and new records and notes on other Harpactorini (Hemiptera: Heteroptera: Reduviidae: Harpactorinae) from South America - Gil-Santana, Hélcio R.; Forero, Dimitri (Zootaxa, 2009)
A new species of Notocyrtus, N. costai sp. nov. is described from Surinam. Photographs in dorsal and lateral views are provided for this new species. Notocyrtoides Carvalho, Costa & Gil-Santana, 2001, is considered to be a junior synonym of Coilopus Elkins, 1969, with N. tuberculatus Carvalho, Costa & Gil-Santana, 2001, as a junior synonym of C. vellus Elkins, 1969. New occurrences of other Harpactorini species are recorded for the first time from Brazil: Harpactor rhombeus (Erichson, 1848), Orbella exceptio Bérenger, 2007, and Orbella putshkovi Bérenger, 2007; and from Surinam Notocyrtus dorsalis (Gray, 1832). Remarks on the color variation of these species and Notocyrtus ricciae Gil-Santana & Costa, 2001, and Notocyrtus dispersus Carvalho & Costa, 1992, are given.